The best of intentions [large type] - Mason, Susan Anne (Mason, Susan Anne. Canadian crossings, 2018)
After WWI Grace Abernathy is determined to reunite with her family, crossing an ocean to convince her widowed sister to return home to England. Yet Toronto holds more tragedy: her nephew, Christian, is in the custody of his paternal relatives, the formidable Easton family, who rejected Grace's sister because of her low social status. Unconvinced the Eastons can be fitting caretakers, Grace jumps at the chance to be Christian's nanny. And in the course of her new position, she's shocked to find herself falling for his guardian, Andrew Easton.